Evaluation of subgingival microbiota around single tooth implants - Amit Kumar Tamrakar; G. Murali; Shyam Singh; R. Shakila (Journal of Oral Biology and Craniofacial Research)
Objectives: 1. To provide information about the subgingival microbiota around single tooth implants.2. To assess the subgingival microbial flora around the teeth adjacent to single tooth implants.3. To clinically evaluate the gingival health surrounding the single-tooth implants. Methods: Patients undergoing the single-tooth implant replacements, were selected as subjects for the study. The natural teeth adjacent to implant sites were taken as control sites. Clinically each peri-implant gingival tissue health was evaluated. Subgingival plaque samples were removed with sterile curette and evaluated for microbial flora, by microscopic examinations. Bacterial cultures of samples studied. The similar procedure was followed for the control sites also. Finally the data collected were statistically analyzed and interpreted. Results: The subgingival microbiota around single tooth implants was cultured and studied. Enterobacter species, Klebsiella pneumonia, Pseudomonas aeruginosa and Streptococcus species were predominantly found. Klebsiella pneumonia and Pseudomonas aeruginosa were found more frequently around implant sites than control sites. Anaerobic Bacteroides species were found in only one case around the implant site. Conclusions: Prevention and control of bacterial infection in the peri-implant region are among the key factors in determining the long term success or failure of dental implant therapy. The thorough knowledge about the subgingival microbiota around the healthy and diseased peri-implant mucosa is needed to determine the overall outcome of implant therapy.